Application of FF-QuantSC for the Precise Estimation of Fetal Fraction in Non-invasive Prenatal Testing in Two SRY-Translocation Cases - Zeng, Yan; Gao, Jiong; Yuan, Hua; Zhou, Lijun; Cheng, Dehua; Che, Ming; Qian, Yandi; Fan, Jiaming; Zhang, Lifang; Qian, Feiyan; Gao, Yuling; Luo, Tingting; et al. (Frontiers in Genetics, 2020)
Background: Non-invasive prenatal testing (NIPT) is a commonly employed clinical method to screen for fetal aneuploidy, while the Y chromosome-based NIPT method is regarded as the gold standard for the estimation of fetal fraction (FF) of male fetuses. However, when the fetus has a derivative Y chromosome thereby containing a partial Y chromosome, the Y chromosome-based NIPT method cannot accurately calculate FF. Therefore, alternative methods to precisely calculate FF are required. Methods: Two prenatal cases could not be detected effectively using the Y chromosome-based NIPT method because of low FF. According to the Y chromosome-based method, the FF of the fetuses were 1.730 ± 0.050% (average gestation week: 18+1) and 2.307 ± 0.191% (average gestation week: 20+0) for cases 1 and 2, respectively. Using various genetic diagnostic techniques, including the BoBs™ assay, karyotype analysis, improved nucleolus-organizing region (NOR)-banding analysis, Affymetrix CytoScan 750K Array, and fluorescence in situ hybridization (FISH) analysis, we determined the genetic defects of two fetuses with translocations of the SRY locus. Further, we reassessed the FF using FF-QuantSC and X chromosome-based methods. The distribution diagram of reads for chromosome Y was also analyzed. Results: The FF of the fetuses determined by FF-QuantSC were 10.330% (gestation week: 18+4) in case 1 and 9.470% (gestation week: 21+4) in case 2, while the FF of the fetuses determined using the X chromosome-based method were 8.889% (gestation week: 18+4) in case 1 and 2.296% (gestation week: 21+4) in case 2. Both the distribution diagrams of reads for chromosome Y of the two cases showed the deletion in the long arm of the Y chromosome. Conclusion: For repeatedly low FF samples detected using the Y chromosome-based NIPT method for a long gestational week, we believe that FF-QuantSC and distribution diagrams of reads could be used as a supplement to NIPT, especially for rare cases of sex reversal caused by SRY translocation.